How to understand the Israel-Palestine conflict from the perspective of International Humanitarian Law - Llanos Villanueva, Luz Amparo (2024)
This article presents a line of analysis that discusses international law and international politics with key elements such as the importance of the history of both peoples involved in this conflict. The main question the author tries to pose to the reader is: to what extent in this controversial historical conflict have international organizations been fulfilling their roles, taking into account the legal framework that legitimizes them? The first part introduces the reader to a brief summary of the most important historical facts that make this conflict one of the most important today. In the second part, the article presents the importance of humanitarian law and its fulfillment in the face of the Israel-Palestine conflict. Finally, the author highlights a not uncommon element for analyzing the conflict, which is the participation of the United Nations in assisting the Israel-Palestine conflict, but especially the possibility of strengthening the United Nations peacekeeping forces for humanitarian aid that goes hand in hand with the basic objectives of international humanitarian law.